The Annual Difference: How a Four-Century Debate between Confucian, Daoist, and Buddhist Thinkers on a Problem of Classical Exegesis Shaped a Predictive Mathematical Construct - Morgan, Daniel Patrick (Religions, 2024)
In China, the precession of the equinoxes was conceptualized as an “annual difference” (suicha 歲差) between the tropical and sidereal year. The idea was introduced in the fourth century, it saw universal acceptance from the eighth century on, and it was in the four centuries in between that it was tried, debated, and spread whilst a Mediterranean-origin concept thereof arrived from India. Its four-century journey from fringe idea to universal truth is a well-studied point of interest in the history of astronomy. In this article, we will shift focus to the idea’s polymathic protagonists and epistemic foundations to explore how a scientific idea was born, debated, transmitted, and taught in Confucian commentary and, no less important, how politics, geography, regional schools, foreign transmission, and the Buddhist and Daoist religions shaped how thinkers engaged with it as individuals and as communities. Inspired by the work of Chen Kanli and Randall Collins, the goal is to show that there is nothing simple or inexorable about how even an empirically useful tool of predictive astronomical modeling is received in the relevant expert community, as it is but one element in a complex network of people and ideas aligning and opposing in ever-evolving strategies to assert relevance.